The Pneumatological Imagination : A Theological Concert in Honor of Amos Yong - Oliverio, L. William; Stephenson, Christopher A. (Global Pentecostal and Charismatic Studies, 2026)
This collection is one of the most comprehensive elaborations of "the pneumatological imagination"-a disposition to God and the world shaped by the doctrine of the Holy Spirit. Scholars in theology, biblical studies, history, and theological education interact with, build on, and critically evaluate this highly important hermeneutical principal in conversation with the theology of Amos Yong and in its own right. The contributors represent several different cultural and ethnic contexts, Church traditions, and kinds of institutions of higher education. They will guide you from beginning understandings of the pneumatological imagination to sophisticated deployments of it through a concert in honor of their colleague and friend.